The Relation of Language Learning Strategy use with Self-efficacy, Motivation, and English Language Achievement - Khodadad, Masoomeh; Kaur, Jagdish (Journal of Modern Languages, 2019)
Greater emphasis has been placed on learners and the procedure through which L2 learning happens. Hence, this study aims to investigate the effect of English learning strategy use on intermediate students’ English achievement. However, in this research strategy use is considered in relation to motivation and self-efficacy, to which less attention has been paid. An adapted version of Gardner’s (2001) model was used. 240 EFL students studying at the Iran Language Institute were administered different questionnaires to collect data. Findings of the study using Structural Equation Modeling revealed that the use of strategies directly affected English achievement. However, when strategy use was influenced by self-efficacy and motivation, it had a stronger effect on English achievement. Specifically, strategy use was more dependent on self-efficacy than motivation. Therefore, to enhance the English language achievement of Iranian EFL students, self-efficacy and motivation on which learners’ strategy use depends must be given due attention.